To all my nurses ... - S. Goodall (AOSIS, 1984)
Professor Julius Hackethal is a wellknown general surgeon in West Germany. In 1975 he made plans to emigrate to South Africa because he was convinced he could carry out his ideas of an ideal patient-friendly clinic here.